Departmental Engagement in Doctoral Professional Development: Lessons from Political Science - Berdahl, Loleen; Malloy, Jonathan (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2019)
There is widespread discussion about the need to develop and enhance the career prospects of PhD graduates, and many Canadian universities are seeking to provide professional development programs and mentorship specifically for doctoral students. This paper considers doctoral career preparation from the department level through an in-depth examination of how Canadian political science departments approach the issue, drawing on a survey of department chairs. We find that departments are supportive of professional development; while departments are not in the position to provide extensive programs and struggle to integrate efforts systematically, they are well-positioned to participate in collaborative approaches and welcome improved communication and coordination. We argue that graduate faculties should consult with departments and engage them in professional development program design, perhaps tailoring to specific disciplines as needed, and that departments should look for opportunities to work with graduate faculties before initiating their own programs.